Radionuclide imaging for feasibility of target left ventricular lead placement in patients with heart failure scheduled for cardiac resynchronization therapy - A. B. Romanov; S. M. Minin; N. A. Nikitin; D. V. Losik; I. G. Stenin; D. A. Yelesin; R. E. Zhizhov; A. G. Filippenko; I. L. Mikheenko; S. N. Artemenko; E. V. Fisher; V. V. Baranova; et al. (Российский кардиологический журнал)
Aim. To assess the feasibility and effectiveness of target left ventricular (LV) lead placement using the radionuclide imaging and changes of myocardial perfusion (MP) and cardiac sympathetic neural activity (SNA) in patients with heart failure (HF) before and after cardiac resynchronization therapy (CRT).Material and methods. This prospective, observational study included 15 patients (9 men, 61 [58; 72] years old) with HF who were referred for CRT Patients underwent radionuclide imaging with assessment of MP and cardiac SNA with 123I-MIBG. All patients underwent implantation of CRT devices with target LV lead placement. Target LV lead placement was performed in accordance with preoperative data on 99mTc-MIBI myocardial perfusion scintigraphy and intraoperative data on coronary sinus (CS) anatomy. After successful implantation, patients were assigned to the group 1 (target LV lead placement). In case of targeted placement inability, the LV lead was implanted into the available CS branches — group 2. The patients were followed up within period of 3-6 months after surgery.Results. Target LV lead placement was performed in 9 (60%) of 15 patients (group 1). In 6 (40%) of 15 patients, targeted implantation was not possible and LV lead was implanted anatomically (group 2). The follow-up period was 4 [3.5; 4.5] months. Patients from group 1 demonstrated a significant improvement of myocardial perfusion compared with preoperative data: summed stress score improved from 16,2±12,2 to 10,8±12,8 (p=0,007), summed rest score — from 15,2±12,5 to 9,8±12,9 (p=0,008), respectively. A significant change in the 123I-MIBG scintigraphy of cardiac SNA was also observed: an improvement in the delayed heart/mediastinum ratio from 1,4±0,2 to 1,63±0,1 (p=0,02) and an improvement in the washout rate from 13,2±5,6% to 7,8±4,7% (p=0,026), respectively. These parameters did not show any significant difference between the groups and within the anatomical positioning group.Conclusion. In patients with HF scheduled for CRT the target LV lead placement using radionuclide imaging results in an improvement of myocardial perfusion and cardiac SNA compared with baseline data and does not have differences compared to anatomical positioning. Further studies are needed to assess the role of radionuclide imaging in CRT.